Pelatihan Pengolahan Mie Basah dan Permen Gummy Berbasis Buah Buni untuk Meningkatkan Asupan Gizi dan Ekonomi Masyarakat - Meda Canti; Yanti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Intake of foods rich in nutritional content, such as buni fruit, can be a solution to overcome vitamin C deficiency. However, the use of buni fruit is still limited due to the lack of public knowledge in processing buni fruit. Therefore, training is needed to process buni fruit into products with added value, such as wet noodles and gummy candy. This training aimed to provide insight into public knowledge regarding the benefits and processing of buni fruit into wet noodle products and gummy candy. The method for implementing this activity was training (delivery of material and demonstration). As many as 100% of participants strongly agreed that this training was beneficial and provided insight into the nutritional benefits and processing of buni fruit. Participants succeeded in making wet noodles and gummy candy independently. Continuous assistance is needed for participants who want to become entrepreneurs with processed wet noodle products and gummy candy based on buni fruit.